DETERMINATION OF HEPCIDIN CONCINTRATION AND MANY HEMATOLOGICAL AND BIOCHEMICAL VARIATIONS IN PATIENTS WITH DIABETESTYPE 2 IN BALAD CITY - Duraid Jafar Toma Al-harbawi; Wedad Mahmood Lahmood Al-obaidi (Tikrit Journal of Pure Science, 2023)
Introduction: Diabetes is a group of metabolic diseases characterized by excessive blood sugar caused by a defect in insulin secretion or function, there are two main types of diabetes: namely, insulin-dependent diabetes mellitus (Type I) known as childhood diabetes, The second type is non-insulin-dependent diabetes mellitus, and usually affects adults after the age of forty. Hepcidin is the main organizer of the iron  metabolism inHuman and in the rest of mammals.